Personality and emotional intelligence in second language learning - Ożańska-Ponikwia, Katarzyna (Cambridge Scholars Publishing, 2018)
This book addresses a particularly important area of second language acquisition research, specifically the factors that mediate learning outcomes in learning a second or foreign language. It provides a comprehensive, up-to-date overview of studies in the field of second language learning and L2 use from the point of view of personality traits and emotional intelligence. It also presents results of a mixed-method study researching the possible influence of these variables on the process of learning a second language. Furthermore, the book represents the first systematic exploration of the role.